2020
DOI: 10.5194/os-16-167-2020
|View full text |Cite
|
Sign up to set email alerts
|

The impact of meltwater discharge from the Greenland ice sheet on the Atlantic nutrient supply to the northwest European shelf

Abstract: Abstract. Projected future shoaling of the wintertime mixed layer in the northeast (NE) Atlantic has been shown to induce a regime shift in the main nutrient supply pathway from the Atlantic to the northwest European shelf (NWES) near the end of the 21st century. While reduced winter convection leads to a substantial decrease in the vertical nutrient supply and biological productivity in the open ocean, vertical mixing processes at the shelf break maintain a connection to the subpycnocline nutrient pool and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…Second, however, Laufkötter et al (2013) and Matsumoto et al (2010) used a fully coupled Earth System Model that accounts for feedbacks between atmospheric and oceanic processes while our modelling framework relies on a prescribed atmospheric state. Third, the global response of hydrodynamical and biogeochemical processes to changes in the physical climate has been shown to strongly vary from one model to the other (Bopp et al, 2013;Kwiatkowski et al, 2017Kwiatkowski et al, , 2020Laufkötter et al, 2015;Mathis & Mikolajewicz, 2020;Matsumoto et al, 2010). Thus, the trend in the marine NPP is also strongly affected by the different architectures and formulations for hydrodynamical and biogeochemical processes in different models.…”
Section: Role Of Changes In the Physical Climate For Oceanic Carbon Cyclingmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, however, Laufkötter et al (2013) and Matsumoto et al (2010) used a fully coupled Earth System Model that accounts for feedbacks between atmospheric and oceanic processes while our modelling framework relies on a prescribed atmospheric state. Third, the global response of hydrodynamical and biogeochemical processes to changes in the physical climate has been shown to strongly vary from one model to the other (Bopp et al, 2013;Kwiatkowski et al, 2017Kwiatkowski et al, , 2020Laufkötter et al, 2015;Mathis & Mikolajewicz, 2020;Matsumoto et al, 2010). Thus, the trend in the marine NPP is also strongly affected by the different architectures and formulations for hydrodynamical and biogeochemical processes in different models.…”
Section: Role Of Changes In the Physical Climate For Oceanic Carbon Cyclingmentioning
confidence: 99%
“…Local changes in ocean circulation seem to be of even larger importance in the coastal ocean, where hydrodynamical circulation While decadal variability of the ocean system currently prevents definite conclusions regarding the impacts of climate-induced changes on the biological productivity from observations alone, modelling studies have addressed these perturbations at global (Bopp et al, 2013;Laufkötter et al, 2013Laufkötter et al, , 2015Matsumoto et al, 2010) and regional scales (Fennel et al, 2006;Frischknecht et al, 2018;Holt et al, 2016Holt et al, , 2018Mathis et al, 2019). In Laufkötter et al (2013) to changes in the physical climate has been shown to strongly vary from one model to the other (Bopp et al, 2013;Kwiatkowski et al, 2017Kwiatkowski et al, , 2020Laufkötter et al, 2015;Mathis & Mikolajewicz, 2020;Matsumoto et al, 2010). Thus, the trend in the marine NPP is also strongly affected by the different architectures and formulations for hydrodynamical and biogeochemical processes in different models.…”
Section: Role Of Changes In the Physical Climate For Oceanic Carbon C...mentioning
confidence: 99%
“…The ensemble simulation dataset represents changes in ocean density and currents as well as meteorological conditions including atmospheric water transport due to the enhanced radiative forcing under climate change. The ensemble is created by starting the global model from different historical states of the years 1950-1959 of three previous simulations with the same model system (Mathis and Mikolajewicz, 2020). For the downscaling of the global simulations, its 6-hourly outputs serve as a forcing for the MPIOM-REMO regional climate modelling framework, which, in turn, provides the boundary forcing for the SCHISM simulations analysed in this study.…”
Section: Global Climate Scenariosmentioning
confidence: 99%
“…Each member of this ensemble covers the period 1950-2005 with the corresponding historical atmospheric pCO2 and their continuation from 2006 to 2099 under the RCP8.5 emission scenario. Members differ from each other only due to different initial states, taken from historical initial states of the years 1950-1959 of three previous simulations with the same model system, which were analyzed by Mathis and Mikolajewicz (2020). An additional control run with constant pre-industrial atmospheric pCO2 (PI) simulated the full period 1950-2099 to obtain information about model-internal variability and possible drifts.…”
Section: Introductionmentioning
confidence: 99%